Evaluation of the effects of various induction drugs with rocuronium bromide on hemodynamics and intubation conditions during rapid sequenced intubation (Annals of Medical Research, 2021)
None
Keywords: s : Anaesthetics intravenous; thiopental, propofol. Anaesthesia techniques; rapid sequence intubation, Intubation; tracheal. Neuromuscular relaxants, rocuronium bromide.